Positional cues and differential gene expression in somatic embryos of higher plants - Racusen, R.H.; Schiavone, F.M.
Much of the organization of higher vascular plants is determined during the formation of the embryo. In addition to the zygotic embryo which results from sexual fertilization in the ovule, many plants are capable of producing embryos from somatic cells. Of particular interest to plant developmental biologists is the phenomenon of somatic embryogenesis in cultures of the domesticated carrot which, because of its tractable nature in experimental manipulations, is presently regarded as a suitable model for studying pattern formatiojn in plants. This short review considers the state of our knowledge concerning the origin and perception of positional information in plant embryos, and the temporal and spatial expression of genes. The available data provide a number of promising leads for cell-cell interactions in embryos, and there are some clear indications that the spatial distribution of certain gene products is correlated with changes in morphology. However, there is, as yet, insufficient evidence with which to forge a link between positional cues and the expression of genes which influence developmental transitions in embryos.
Keywords: SOMATIC EMBRYOGENESIS; CARROT EMBRYOGENESIS; GENE EXPRESSION; POSITIONAL INFORMATION